Complementarity in both plant and mycorrhizal fungal communities are not necessarily increased by diversity in the other. (29th July 2015) - Wagg, Cameron; Barendregt, Christoph; Jansa, Jan; van der Heijden, Marcel G.A.; Mommer, Liesje
Summary Higher species diversity can improve community performance within a species guild when different species complement each other in their use of the available niche, such as through resource partitioning. However, species in one guild of organisms may act as resources for another such that the diversity in one guild alters the realized niche for species in another. Yet, it remains largely untested as to whether diversity in one guild of organisms influences species complementarity in another. The productivity and diversity in plant and arbuscular mycorrhizal (AM) fungal communities can be positively associated with each other through their typically mutualistic exchange of resources. Here, we utilized these two interacting species guilds to determine whether greater diversity in one influences species complementarity in the other. This was performed by creating monocultures and a mixture of a grass, forb and legume in a full factorial design with monocultures and a mixture of four AM fungi. The presence of AM fungi reduced differences in the performance among plant species and greater diversity of fungi generally improved plant productivity over the average of the fungal monocultures. However, plant species complementarity was not greatest with a higher diversity of fungi and was only positive with a particular fungal monoculture. AM fungal abundance was not affected by plant diversity, but was greatly reduced in the grass monoculture compared to the other plant communities. Variation in fungal complementarity among plant communities was low overall and was little influenced by plant diversity. Synthesis. Using a model plant‐mycorrhizal system, our results suggest that the composition rather than the diversity of species within one guild may be more influential in determining how species function within an associated species guild. However, our model system does not represent a broad gradient of diversity in either plant or fungal communities and only assesses the initial growth phase. Nonetheless, our results highlight that changes in species compositions in one species guild can affect the functioning of species diversity in another.